How to resist your rival - Dove, Rachel (Harlequin medical romance, 2023)
Robotics scientist Harper dreams of helping prosthetics patients worldwide. The problem? Infuriating neurosurgeon Dr. Dom. This man raises her temper--and her pulse But despite a series of heated clashes, the layers of his cold exterior begin to melt. Soon, cautious Harper finds resisting her rival an impossible task, as days--and nights --in the lab blur the lines between professional and deeply personal...